2016
DOI: 10.1186/s12918-015-0246-z
|View full text |Cite
|
Sign up to set email alerts
|

UbiSite: incorporating two-layered machine learning method with substrate motifs to predict ubiquitin-conjugation site on lysines

Abstract: BackgroundThe conjugation of ubiquitin to a substrate protein (protein ubiquitylation), which involves a sequential process – E1 activation, E2 conjugation and E3 ligation, is crucial to the regulation of protein function and activity in eukaryotes. This ubiquitin-conjugation process typically binds the last amino acid of ubiquitin (glycine 76) to a lysine residue of a target protein. The high-throughput of mass spectrometry-based proteomics has stimulated a large-scale identification of ubiquitin-conjugated p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 63 publications
(60 reference statements)
0
36
1
Order By: Relevance
“…RNA-binding properties of ZBP1 were predicted using protein-RNA–binding prediction analytical tools BindN, catRAPID, and aaRNA ( Wang and Brown, 2006 ; Agostini et al, 2013 ; Li et al, 2014 ). UbPred and UbiSite servers were used to predict potential ubiquitination sites in ZBP1 ( Radivojac et al, 2010 ; Huang et al, 2016 ). i-TASSER server was used to predict full-length ZBP1 structure ( Roy et al, 2010 ).…”
Section: Methodsmentioning
confidence: 99%
“…RNA-binding properties of ZBP1 were predicted using protein-RNA–binding prediction analytical tools BindN, catRAPID, and aaRNA ( Wang and Brown, 2006 ; Agostini et al, 2013 ; Li et al, 2014 ). UbPred and UbiSite servers were used to predict potential ubiquitination sites in ZBP1 ( Radivojac et al, 2010 ; Huang et al, 2016 ). i-TASSER server was used to predict full-length ZBP1 structure ( Roy et al, 2010 ).…”
Section: Methodsmentioning
confidence: 99%
“…Ubiquitination of human PEG10 was predicted by UbiSite (http://csb.cse.yzu.edu.tw/UbiSite/prediction. php) [48], BDM-PUB: Prediction of Ubiquitination sites with Bayesian Discriminant Method (http: //bdmpub.biocuckoo.org), and UbPred (predictor of protein ubiquitination sites) (http://www.ubpred. org/cgi-bin/ubpred/ubpred.cgi) [49] web servers, using default parameters.…”
Section: In Silico Analysismentioning
confidence: 99%
“…Due to the difficulty of observing the conserved motifs from a large-scale sequence dataset, MDD has been utilized to cluster a group of aligned phosphorylated peptides into subgroups that show statistically significant motifs [ 20 ]. Previous studies [ 31 , 35 , 40 42 ] have demonstrated the effectiveness of the clustering of modified sequences into subgroups prior to the construction of predictive models. For this investigation, MDD was applied using public software, MDDLogo [ 31 ], to cluster all the sequence fragments of the positive training dataset.…”
Section: Methodsmentioning
confidence: 99%